Analisis Stabilitas Steel Modular Scaffolding (Perancah Baja) pada Pekerjaan Bangunan Struktur Tailrace Surgetank di Proyek Pembangunan PLTA Asahan 3 - Marah Husin Fadli Lubis; Johannes Taringan (Jurnal Syntax Admiration, 2023)
Modular steel scaffolding is one type of scaffolding that is now widely used in the world of construction. To prevent formwork and scaffolding failure due to loads and other factors, the formwork and scaffold construction must meet the requirements for strength, rigidity and stability. Steel plans are generally slender and require stability analysis. The results are influenced by imperfection (non-linear geometry) and inelastic conditions (non-linear material). In analyzing the stability of steel scaffolding structures, it is necessary to analyze the load capacity by means of numerical modeling. Analysis of the maximum strength of steel structures requires computer analysis of elastic second order analysis based on the Direct Analysis Method (DAM). A new computer-based method contained in the latest Indonesian SNI for steel planning (SNI 1729-2015). In the analysis, the loading is given in stages, and each stage will be evaluated for strength available and strength needed. The maximum load is considered to have been reached when the available strength is the same as the required strength. The scaffolding model consists of 25 levels, each level is 1.5 meters high. Based on the results of the analysis and evaluation of the cross-section strength of the elements reviewed, the maximum capacity of the scaffold level 1 is 68.48 kN. And the maximum capacity load on the 25 story scaffolding is 51.30 kN. The bearing capacity of the elements is reduced, due to the presence of large moments